Adaptive view synthesis optimization for low complexity 3D-HEVC encoding. (April 2018) - Tan, Songchao; Ma, Siwei; Wang, Shanshe; Wang, Shiqi; Zhang, Xinfeng; Gao, Wen
Abstract: Depth compression plays an important role in 3D video coding with the typical texture-plus-depth representation. In this paper, to reduce the encoding complexity of depth map, we propose a low complexity adaptive View Synthesis Optimization scheme for the 3D extension of high efficiency video coding (3D-HEVC) standard. More specifically, we distinguish the coding tree units (CTUs) based on the influence of depth map compression on the quality of rendered synthesized view, and classify them into two categories, including synthesized view distortion change (SVDC) based and view synthesis distortion estimation (VSDE) based CTUs. In this manner, we can dynamically distinguish the CTUs and apply different rate-distortion optimization strategies. Moreover, for VSDE based CTUs, a new distortion model is proposed to infer the distortion of the synthesized view based on the depth distortion and texture characteristics. As such, we can achieve a good trade-off between the rate-distortion performance and computational complexity for depth map coding. Experimental results also confirm that the proposed scheme is effective in reducing the encoding complexity with ignorable rate-distortion performance loss compared with the state-of-the-art scheme in the 3D-HEVC platform.